Case Report: Difficulties faced by a home oxygen therapy patient who died after the Fukushima Daiichi nuclear power plant accident - Yamamura, Momoka; Sawano, Toyoaki; Ozaki, Akihiko; Zhao, Tianchen; Yamamoto, Chika; Montesino, Stephanie; Kawashima, Moe; Uchi, Yuna; Yoshimura, Hiroki; Kitazawa, Kemmei; Marui, Hidenori; Tsubokura, Masaharu (Frontiers in Public Health, 2024)
Following the Great East Japan Earthquake (GEJE) and the Fukushima Daiichi nuclear power plant accident in 2011, mandatory evacuation orders were issued to residents living near the nuclear power plant in Fukushima prefecture, including some patients receiving home oxygen therapy. Although the vulnerability of patients with home oxygen therapy (one of the population groups most vulnerable to disasters) has been noted, there is little information on the health effects of evacuation in the event of a radiation disaster. A 90-year-old man diagnosed with chronic obstructive pulmonary disease since the age of 70, and lived in a town located approximately 20 km south of the nuclear power plant, died 8 months after the disaster due to worsening health conditions. This case reveals the potential for both physical and psychological burdens experienced by vulnerable groups like patients undergoing home oxygen therapy during evacuations in times of disaster. Although it is only a case report and the information is limited, severe respiratory distress requiring home oxygen therapy may present a significant risk factor for disaster-related deaths, especially in cases where evacuations are prolonged, such as in nuclear disasters. Due to the challenge of obtaining prompt public support immediately after a disaster, home oxygen therapy patients may need to prioritize self-help and mutual assistance in their disaster preparedness efforts.